Pengembangan Bakat dan Budaya Organisasi dengan Mediasi Perilaku Inovatif pada Kinerja Inovasi Merek - Hermansah, Asep; Winasis, Shinta (DFAME Digital Financial Accounting Management Economics Journal, 2026)
This study investigates the influence of talent development and organizational culture on brand innovation performance through the mediating role of innovative behavior. Using a quantitative approach, data were collected from 200 respondents representing UMKM in Purwakarta, Indonesia. Structural Equation Modeling with the Partial Least Squares technique was applied to test the proposed relationships. The results indicate that talent development significantly enhances innovative behavior, suggesting that learning and capability-building initiatives stimulate employees to generate and implement new ideas. Organizational culture also shows a positive effect on innovative behavior, highlighting the importance of shared values that support experimentation and openness. Innovative behavior is found to have a direct and positive impact on brand innovation performance, confirming that brand renewal is driven by employee-level innovation activities. Moreover, innovative behavior mediates the effects of both talent development and organizational culture on brand innovation performance, demonstrating that organizational inputs must be translated into behavioral actions to produce meaningful innovation outcomes. These findings extend the Innovative Work Behavior perspective by linking internal management practices with strategic branding results. The study provides practical implications for UMKM managers by emphasizing the need to integrate training systems and cultural values with innovation-oriented goals. Overall, the research contributes to a deeper understanding of how human-centered organizational practices foster sustainable brand innovation.